Alteration of Oxidative Phosphorylation as a Possible Mechanism of the Antifungal Action of P-Coumaric Acid Against Botrytis Cinerea - Cotoras-Tadic, M; Mendoza-Espinola, L; Mendoza-Espinola, L (2017)
Aims: The aim of this study was to analyse the mechanism of action of p-coumaric acid against isolate B05·10 of Botrytis cinerea. For this purpose, the effect of this compound on cell membrane, cell wall and oxidative phosphorylation was determined. Induction of oxidative stress triggered by this compound was also studied. Methods and Results: p-coumaric acid showed antifungal effect on the mycelial growth. Additionally, the compound was able to retard the germination of Botrytis cinerea conidia. The mechanism of action of this compound was analysed using fluorescent probes. p-Coumaric acid did not affect the integrity of cell wall and plasmatic membrane and neither produced oxidative stress. Finally, it was shown that the compound produced an increase in oxygen consumption. Conclusions: p-coumaric acid performs as a mitochondrial uncoupler in B. cinerea. Its role as an uncoupler of oxidative phosphorylation could be explained to its acidic, nonpolar and planar characteristics. These structural and chemical characteristics would favour ability of p-coumaric acid to pass through cellular membranes. Significance and Impact of the Study: Plant secondary metabolites can be used as an alternative way to control phytopathogenic fungi. The knowledge of the action mechanism of these compounds can contribute to design modified molecules with higher antifungal activity. © 2017 The Society for Applied Microbiology
Keywords: antifungal activity; Botrytis cinerea; mechanism of action; oxidative phosphorylation uncouplers; p-coumaric acid